Perencanaan Strategis Sistem dan Teknologi Informasi pada PT Jasamarga Surabaya-Mojokerto dengan Pendekatan Anita Cassidy - Perdani, Novita; Nurcahyawati, Vivine; Maulana, Yoppy Mirza (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2018)
PT Jasamarga Surabaya-Mojokerto is a toll road entreprise with the main task to build, operate, and maintain Surabaya-Mojokerto toll roads. The Surabaya-Mojokerto toll road passes through 4 regencies (Sidoarjo, Gresik, Surabaya, and Mojokerto) and passes 37 villages with 306.20 hectare of land. PT Jasamarga Surabaya-Mojokerto experience some obstacles in the application of information technology systems. Investments in information technology systems that have been run not support the bussines goals oh the company. Another obstacle is the absence of clustering and priority scale of technology system development. To handle these obstacles, it is necessary to make strategic planning of information system with Anita Cassidy approach for PT Jasamarga Surabaya-Mojokerto. Strategic planning of information system can help companies to implement information technology system that align with business strategy and corporate goals, also can help clustering and determine the direction of development of information technology system.